2006
DOI: 10.1371/journal.pmed.0030441
|View full text |Cite
|
Sign up to set email alerts
|

Complement Lysis Activity in Autologous Plasma Is Associated with Lower Viral Loads during the Acute Phase of HIV-1 Infection

Abstract: BackgroundTo explore the possibility that antibody-mediated complement lysis contributes to viremia control in HIV-1 infection, we measured the activity of patient plasma in mediating complement lysis of autologous primary virus.Methods and FindingsSera from two groups of patients—25 with acute HIV-1 infection and 31 with chronic infection—were used in this study. We developed a novel real-time PCR-based assay strategy that allows reliable and sensitive quantification of virus lysis by complement. Plasma deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
93
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 65 publications
8
93
0
Order By: Relevance
“…[14][15][16] Using a novel real-time PCR-based assay strategy that allows reliable and sensitive quantification of viral lysis by complement, Huber et al documented that complement (sera from HIV-1-infected patients)-mediated lysis activity against the HIV-1 primary virus was higher during chronic disease stages than during the acute phase. 17 They also found that plasma viral load levels during the acute but not the chronic infection phase correlated inversely with the autologous complement lysis activity. 17 These effects were attributed to anti-envelope (Env) Abmediated complement-dependent lysis.…”
Section: Protective Role Of Complement Activation and Ab Immunity In mentioning
confidence: 94%
See 3 more Smart Citations
“…[14][15][16] Using a novel real-time PCR-based assay strategy that allows reliable and sensitive quantification of viral lysis by complement, Huber et al documented that complement (sera from HIV-1-infected patients)-mediated lysis activity against the HIV-1 primary virus was higher during chronic disease stages than during the acute phase. 17 They also found that plasma viral load levels during the acute but not the chronic infection phase correlated inversely with the autologous complement lysis activity. 17 These effects were attributed to anti-envelope (Env) Abmediated complement-dependent lysis.…”
Section: Protective Role Of Complement Activation and Ab Immunity In mentioning
confidence: 94%
“…17 They also found that plasma viral load levels during the acute but not the chronic infection phase correlated inversely with the autologous complement lysis activity. 17 These effects were attributed to anti-envelope (Env) Abmediated complement-dependent lysis. Together, these results indicate that Ab-mediated complement virion lysis develops rapidly and is effective early in the course of infection.…”
Section: Protective Role Of Complement Activation and Ab Immunity In mentioning
confidence: 94%
See 2 more Smart Citations
“…37 Thus for a variety of reasons, even with highly immunogenic envelope constructs, the human B-cell arm of the immune system prefers to not recognize the vulnerable region epitopes of the HIV-1 envelope but rather prefers to recognize regions of the envelope that induce nonneutralizing antibodies. 38 , 39 A number of other types of anti-HIV-1 antibody responses could potentially help control HIV-1 if they were present at the time of transmission, including antibodies that aggregate virions, thus preventing virion movement across mucosal epithelia 40 ; inhibit transcytosis 41 ; fix complement and lyse virions 42 ; inactivate virus through macrophage Fc-mediated uptake; and mediate antibody-dependent cellular cytotoxicity (ADCC). 43 The latter response might be critically important for targeting infected cells because neutralizing antibodies might be inefficient at preventing viral cell-cell transmission.…”
Section: Hiv-1 Transmissionmentioning
confidence: 99%